2022
DOI: 10.7150/ijbs.65030
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase Gamma Recovers Mitochondrial Function and Inhibits Vascular Calcification by Interacted with p53

Abstract: DNA polymerase gamma (PolG) is the major polymerase of mitochondrial DNA (mtDNA) and essential for stabilizing mitochondrial function. Vascular calcification (VC) is common senescence related degenerative pathology phenomenon in the end-stage of multiple chronic diseases. Mitochondrial dysfunction was often observed in calcified vessels, but the function and mechanism of PolG in the calcification process was still unknown. The present study found PolG D257A/D257A mice presented more severe calcification of aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, it has been shown that correcting mitochondrial dysfunction suppresses cardiovascular calcification. 52,53 Previous studies have shown that POVPC increases the production of ROS and impairs mitochondrial function. 18,19 Consistently, we found that POVPC stimulates oxidative stress and mitochondrial dysfunction, as shown by increased cytosolic ROS levels, impairment of MMP, and decreased ATP contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that correcting mitochondrial dysfunction suppresses cardiovascular calcification. 52,53 Previous studies have shown that POVPC increases the production of ROS and impairs mitochondrial function. 18,19 Consistently, we found that POVPC stimulates oxidative stress and mitochondrial dysfunction, as shown by increased cytosolic ROS levels, impairment of MMP, and decreased ATP contents.…”
Section: Discussionmentioning
confidence: 99%
“…Local ROS generation does not only lead to mitochondrial damage but also affects the redox status. Moreover, it has been shown that correcting mitochondrial dysfunction suppresses cardiovascular calcification 52,53 . Previous studies have shown that POVPC increases the production of ROS and impairs mitochondrial function 18,19 .…”
Section: Discussionmentioning
confidence: 99%